2014
DOI: 10.1007/s11356-014-3874-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between viral detection and turbidity in a watershed contaminated with group A rotavirus

Abstract: Enteric viruses are present in aquatic environments due to contamination by raw sewage, even in the absence of fecal coliforms, which are considered to be significant indicators when it comes to microbial water quality assessment. This study investigated the presence of group A rotavirus (RVA) in surface water from a river basin in Minas Gerais, Brazil, assessing the influence of the urbanization, the rainfall, and the microbiological and physico-chemical parameters regarding water quality. Forty-eight surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
1
5
0
2
Order By: Relevance
“…), although other studies with environmental samples in the country showed higher frequency of this virus in rainy seasons (Assis et al . ; Vieira et al . ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…), although other studies with environmental samples in the country showed higher frequency of this virus in rainy seasons (Assis et al . ; Vieira et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…), it is still one of the most important viral contaminant in environmental samples (Assis et al . ; Elmahdy et al . ; Vieira et al .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Fongaro et al [28] detected up to 65% positive samples in all seasons, which indicated RV prevalence during the year, although this was found to be higher in the winter season. Assis et al [40] detected 54.1% of RV in winter and spring seasons as well as 70.8% during the summer, thus indicating that the transmission of these enteric viruses resulted in higher infection rates through the winter and spring seasons, as stated by the Center for Disease Control and Prevention [41]. Patel et al [42] indicated that transmission patterns, host behavior and susceptibility may contribute to the seasonal prevalence of RV, along with climate conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the traditional oven drying method is unsuitable for our tests, and we need a new way to accurately and rapidly obtain particle concentrations. Previous studies have shown that the turbidity and concentration of particles have a close relationship (Assis et al, 2015). Thus, correlations between turbidity and concentration were studied.…”
Section: Relationship Between Turbidity and Concentrationmentioning
confidence: 99%